An engineering perspective on the microstructure and compression properties of the seagull Larus argentatus feather rachis. (November 2019) - Zou, Meng; Zhou, Jianfei; Xu, Lihan; Song, Jiafeng; Liu, Shengfu; Li, Xiujuan
Highlights: The configuration, structure and compression properties of the seagull Larus argentatus feather rachis were investigated. There are differences in compression properties of feather rachis from different parts of the body of L. argentatus . The L. argentatus feather rachis has excellent compression resistant properties, deriving from the effects of structural factors. Abstract: The feathers of the seagull Larus argentatus are lightweight but can withstand high alternating stresses and exhibit excellent stiffness and strength. The shaft is an important part of the feather, with the functions of body protection and supporting flight. In this study, the microstructure properties of L. argentatus feather rachis were analysed by scanning electron microscopy (SEM). These analysis methods enabled the configuration, structure and compression properties of the rachis to be investigated. The results indicated that the rachis was composed of the outer cortex and the inner medulla. The cortex had a continuous layered nano-fibre composite structure, which bears, transmits, absorbs and disperses the compression force. The medulla had bubble-like cells with a porous-fibre structure, which rapidly absorbs, transmits and consumes compression force and is a suitably lightweight material for flight. Axial compression tests showed that the rachis from primary feathers had the best energy absorption and that from secondary feathers had the best compressive strength. The compressive strength might have something to do with the ratio of cortical area to medullary area. When the moisture content in the rachis increased, the compressive strength of feather rachis in different parts would decrease. These results indicate that the L. argentatus feather rachis have excellent compression resistance properties, deriving from structural factor.